FACTORS RELATED TO MEASLES IMMUNIZATION PROVISION IN CHILDREN AGED 10-12 MONTHS IN THE WORKING AREA OF LHOONG COMMUNITY HEALTH CENTER, ACEH BESAR REGENCY, IN 2022 - amatullah, husnun; Sari, Yuni; Salmiani Abdul Manaf (Department of Midwifery, Health Polytechnic of Aceh, 2025)
Background: Measles in Indonesia is a health problem that must be addressed because the cases remain high and outbreaks of the disease (KLB). The distribution of suspected measles cases is almost in all provinces. In 2018, there were 8,429 cases, with 85 suspected measles cases, which is significantly lower than the 15,104 cases with 349 KLB reported in 2017. Subjects and Method: This study employs a descriptive and analytical approach with a cross-sectional design. The population in this study consisted of all mothers with babies aged 10 to 12 months. Sampling was conducted using simple random sampling, involving 73 respondents. Data processing used the chi-square test. Results; The results of the chi-square test showed that there was a relationship between knowledge (p-value = 0.000), the role of officers (p-value = 0.024) and family support (p value = 0.000) with the provision of measles immunization in the Lhoong Health Center working area, the Regency of Aceh Besar. Conclusion: A relationship was found between knowledge, the role of officers, and family support in the provision of measles immunization.